LEUKOTRIENE RECEPTORS STATE IN CHILDREN WITH BRONCHIAL ASTHMA - Khalmatova, , Barno T. (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the workis to study the level of leukotrienes C4D4E4 in children with bronchial asthma and evaluate the effectiveness of the therapy. Materials and methods. The present research work was performed at the Department of Allergology of the Tashkent Medical Academy Clinic. In total 92 children with bronchial asthma underwent examination during the disease exacerbation. The control group included 23 rather healthy children of the same age. The diagnosis of bronchial asthma is established in accordance with the International Consensus on Diagnosis and Therapy of BA. Results and discussion. According to the aim of our work, we researched the level of leukotrienes С4D4Е4 in urine of 92 children with BA. Among them, there were 62 children with Step 1of BA (67.4%), and 30 children with Step 2 (32.6%). Comparative analysis of the initial data revealed a significant increase of LT release in 72 (78.3%) patients with cough form of BA. In 20 patients with Step 1 of BA, LT values were at the upper limit of the norm (1, 0 ± 0.01). 15 children with Step 2of BA showed an increase in the level of LT more than 5 times in comparison with the admissible norm (p < 0.05).Conclusion. The significant role of LT in the formation of allergic inflammation of the respiratory tractat BA in children has been confirmed. The prescription of cis-ALT (montelukast) is justified both as a monotherapy for mild persistent BA and in combination with IGCS in patients with moderate BA.